Heterologous Expression of Arabidopsis AtARA6 in Soybean Enhances Salt Tolerance - Hong, Zhipeng; Li, Yang; Zhao, Yang; Yang, Mingyu; Zhang, Xiaoming; Teng, Yuhan; Jing, Linjie; Kong, Danxun; Liu, Tongxin; Li, Shuanglin; Meng, Fanli; Wang, Qi; et al. (Frontiers in Genetics, 2022)
Salt damage is an important abiotic stress affecting the agronomic traits of soybean. Soybeans rapidly sense and transmit adverse signals when salt-damaged, inducing a set of response mechanisms to resist salt stress. AtARA6 encodes a small GTPase, which plays an important role in Arabidopsis vesicle transport and salt tolerance. In this study, we transformed the Arabidopsis gene AtARA6 into the cultivated soybean Shen Nong 9 (SN9). To investigate the salt tolerance pathways affected by AtARA6 in soybean, we performed transcriptome sequencing using transgenic soybean and wild-type (SN9) under salt treatment and water treatment. Our results suggest that AtARA6 is involved in the regulation of soybean SNARE complexes in the vesicle transport pathway, which may directly strengthen salt tolerance. In addition, we comprehensively analyzed the RNA-seq data of transgenic soybean and SN9 under different treatments and obtained 935 DEGs. GO analysis showed that these DEGs were significantly enriched in transcription factor activity, sequence-specific DNA binding, and the inositol catabolic process. Three salt-responsive negative regulator transcription factors, namely MYC2, WRKY6, and WRKY86, were found to be significantly downregulated after salt treatment in transgenic soybeans. Moreover, four genes encoding inositol oxygenase were significantly enriched in the inositol catabolic process pathway, which could improve the salt tolerance of transgenic soybeans by reducing their reactive oxygen species content. These are unique salt tolerance effects produced by transgenic soybeans. Our results provide basic insights into the function of AtARA6 in soybeans and its role in abiotic stress processes in plants.